Globalization and marginalization in contemporary Asia: migration, class, and capitalism in Tash Aw’s Five Star Billionaire and We, the Survivors - Chi Miao (Humanities & Social Sciences Communications)
Abstract Drawing on the theoretical framework of globalization from below, this article examines how global capitalism complicates the lived experiences of racially and socioeconomically marginalized groups in contemporary Asia. Through a close reading of Five Star Billionaire and We, the Survivors, two Anglophone novels by Chinese Malaysian author Tash Aw, the analysis explores the intersection of race, class, and globalization, revealing how neoliberal capitalism entrenches social immobility and exploitation within and beyond Malaysia. While Five Star Billionaire critiques the illusory promises of upward mobility for disenfranchised Malaysian migrants, We, the Survivors highlights the cyclical entrapment of migrant laborers within Malaysia’s racialized capitalist hierarchies. Both novels subvert metropolitan readers’ expectations of the “postcolonial exotic” by challenging dominant narratives of Asian prosperity and instead foregrounding systemic inequalities perpetuated by global capitalism. Through detailed textual analysis, this article argues that Aw’s works transcend the categorization of minor literature by offering a universal critique of globalization’s impact on marginalized communities. Ultimately, the novels underscore the failure of neoliberal globalization to foster equitable opportunities, interrogating the structural forces that sustain economic and racial hierarchies in the contemporary global order.